Pour une nouvelle approche du populisme au sein des démocraties représentatives contemporaines - Pierre-Yves Cadalen (École Normale Supérieure de Lyon, 2021)
The academic debates around the rise of so-called populist movements rarely refer to the origins of the tensions structuring representative democracies today. The “democratic deficit” or the “democratic crisis” are expressions that imply the unstructured nature of this moment. We argue here that it points out a structural shift, resulting from the progressive disarticulation between the representative principle and the democratic principle. As both principles defined representative democracy since the 19th century, their disarticulation raises interrogations and produces reactions within the political field: the return of the nation, the possible Constituent Assemblies, as well as the defence of a representative regime deprived of its democratic features are the many political possibilities born out of this disarticulation. The present article develops this thesis and aims at contributing to the theoretical discussions around the current situation of representative democracies, as well as around the so-called populist moment.